Determinan Kemiskinan Multidimensional 34 Provinsi di Indonesia Periode Tahun 2015-2018 - Amartya Intan; Asih Murwiati; I Wayan (Departement of Mathematics Education, 2023)
Poverty is faced by almost all countries in the world. Poverty is the inability of a person to meet basic needs. In calculating the SDGs poverty is placed in a multidimensional framework, namely looking at poverty from various dimensions and looking at the causes of poverty from various sides, which is set forth in SDGs 1